A high-quality, chromosome-level genome assembly of the Black Soldier Fly (Hermetia illucens L.). Issue 5 (12th April 2021) - Generalovic, Tomas N; McCarthy, Shane A; Warren, Ian A; Wood, Jonathan M D; Torrance, James; Sims, Ying; Quail, Michael; Howe, Kerstin; Pipan, Miha; Durbin, Richard; Jiggins, Chris D
Abstract: Hermetia illucens L. (Diptera: Stratiomyidae), the Black Soldier Fly (BSF) is an increasingly important species for bioconversion of organic material into animal feed. We generated a high-quality chromosome-scale genome assembly of the BSF using Pacific Bioscience, 10X Genomics linked read and high-throughput chromosome conformation capture sequencing technology. Scaffolding the final assembly with Hi-C data produced a highly contiguous 1.01 Gb genome with 99.75% of scaffolds assembled into pseudochromosomes representing seven chromosomes with 16.01 Mb contig and 180.46 Mb scaffold N50 values. The highly complete genome obtained a Benchmarking Universal Single-Copy Orthologs (BUSCO) completeness of 98.6%. We masked 67.32% of the genome as repetitive sequences and annotated a total of 16, 478 protein-coding genes using the BRAKER2 pipeline. We analyzed an established lab population to investigate the genomic variation and architecture of the BSF revealing six autosomes and an X chromosome. Additionally, we estimated the inbreeding coefficient (1.9%) of the lab population by assessing runs of homozygosity. This provided evidence for inbreeding events including long runs of homozygosity on chromosome 5. The release of this novel chromosome-scale BSF genome assembly will provide an improved resource for further genomic studies, functional characterization of genes of interest and genetic modification of this economically important species.